Interventional studies in childhood dystonia do not address the concerns of children and their carers. (May 2015) - Lumsden, Daniel E.; Gimeno, Hortensia; Tustin, Kylee; Kaminska, Margaret; Lin, Jean-Pierre
Abstract Aims This study aimed to determine the main concerns/priorities of the parents and carers of children with dystonia referred to our service and whether medical interventional studies addressed these concerns. Methods Records of children assessed by our service from June 2005–December 2012 were reviewed and expressed parental/carer concerns at initial assessment categorized using the International Classification of Functioning (ICF) Framework. Medline, CINAHL and Embase databases were searched for outcome measures of medical and surgical interventional studies in childhood dystonia. Results Data was collected from 273 children and young people with dystonia. The most commonly expressed concerns were: pain (104/273, 38.1%); difficulties in delivering activities of daily-living (66/273, 24.2%), difficulties with hand-use (59/273, 21.6%) and seating (41/273, 15.0%). Literature review identified 70 interventional studies, 46 neurosurgical and 24 pharmacological. The majority of neurosurgical studies (34/46) used impairment scales to measure change, with pharmacological studies typically reporting more subjective changes in motor symptoms. Only a minority of studies used assessments or scales capable of objectively addressing the concerns reported by our cohort. Interpretations Existing interventional studies in childhood dystonia poorly address the main concerns of children with dystonia and their carers, limiting the conclusions which may be drawn as to true impact of these interventions in childhood.